Work Life Balance and Readiness to Change: The Effect of Work from Home to Performance - Ratya Shafira Arifiani; Titiek Ambarwati; Aniek Rumijati (Jurnal Manajemen Universitas Bung Hatta, 2023)
The government's policies on the COVID-19 pandemic have begun to loosen, notably in the education sector.This policy, however, will alter when Covid-19 cases emerge, particularly in Malang City. Covid-19 cases have decreased and a face-to-face learning strategy has been introduced, but this has altered because Covid-19 cases have risen again and have penetrated school clusters, thus some schools have begun with online learning. This study examines the effect of working from home on performance as a result of a new working environment and several policy changes to determine whether it has an impact and an effect on performance. The study then investigates the impact of working from home on change readiness, where changes in work patterns force workers to adapt to technology and become entirely online. Furthermore, given the work imbalance, work-life balance is being researched as a mediating variable by concentrating on activities outside of work that will have an impact on performance. This is an explanatory study that takes a quantitative approach. The results of the data were obtained by distributing questionnaires as primary data, and the respondents of this study were teachers in Malang city. The path analysis tool employed SmartPLS 3.0 software. The findings revealed that work from home has no effect on performance, work from home has no effect on work-life balance, work-life balance has no effect on performance, work from home has an effect on readiness to change, and readiness to change affects performance. Work-life balance does not moderate the effect of working from home on performance, but Readiness to Change does.